2019
DOI: 10.17582/journal.aavs/2019/7.s2.6.11
|View full text |Cite
|
Sign up to set email alerts
|

Stannius Corpuscles in African Catfish (Clarias gariepinus): Histological and Ultrastructure Studies

Abstract: | Stannius corpuscles (SC) are unique endocrine gland in the kidney of bony fish. It plays an important role in regulating calcium haemostasis via secretion of hypocalcine (stanniocalcin) hormone. The structure of Stannius corpuscles has been clarified in several fish species; however, little was elucidated concerning that in African catfish (Clarias gariepinus). Therefore, the aim of the current study is to reveal the structural characteristics of SC in African catfish (Clarias gariepinus) among both sexes. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…The connective tissue septa were determined to be well-vascularized by capillaries or sinusoids. Similar findings were also reported by other researchers in different fish species (Abu Zinadah et al, 2006;Cohen et al, 1975;Karkit et al, 2019;Krishnamurthy & Bern, 1969). Well vascularization of the parenchyma of the glands might be attributed to the function and activity of the gland (Jones et al, 1969).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The connective tissue septa were determined to be well-vascularized by capillaries or sinusoids. Similar findings were also reported by other researchers in different fish species (Abu Zinadah et al, 2006;Cohen et al, 1975;Karkit et al, 2019;Krishnamurthy & Bern, 1969). Well vascularization of the parenchyma of the glands might be attributed to the function and activity of the gland (Jones et al, 1969).…”
Section: Discussionsupporting
confidence: 91%
“…The results showed that 3 to 5 Sc were located on either side of the caudal part of the kidney, both ventrally and dorsally. Similarly, Sc have been reported to be found in the posterior end of the kidney in many teleost species (Abu Zinadah et al., 2006; Bedjargi & Kulkarni, 2014a; Bhattacharyya & Butler, 1978; Cohen et al., 1975; Karkit et al, 2019; Krishnamurthy & Bern, 1969; Oguri, 1966; Tomasulo et al., 1970; Wendelaar Bonga et al., 1977). The number of Sc in adult fish could vary between species, and even among individuals of the same species.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The sinusoidal dilatations in response to hypercalcemia in Labeo rohita is similar to the observations on Clarias batrachus ( Srivastav et al, 1985 , Srivastav and Srivastav, 1988 ). The degeneration among few corpuscular cells observed in Labeo rohita in response to prolonged hypercalcemia is in agreement with the results obtained by Hiroi (1970) on Oncorhynchus sp, Srivastav et al, 1985 , Srivastav and Srivastav, 1988 on Clarias batrachus and histological and ultrastructure studies of CS in African catfish, Clarias gariepinus ( Karkit et al, 2019 ). Advanced evidence that Ca 2+ influx in branchial, intestinal (and likely in renal Ca 2+ transporting cells) is controlled by stanniocalcin (STC) ( Buttler, 1993 , Flik et al, 1993 , Wendelaar Bonga and Pang, 1986a ).…”
Section: Discussionsupporting
confidence: 89%